2019
DOI: 10.1016/j.foodqual.2018.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Using rejection thresholds to determine acceptability of novel bioactive compounds added to milk-based beverages

Abstract: Highlights:  Bioactive casein hydrolysate (NaCaHs) have potential for use in functional foods.  Peptide molecular weight influence the bitterness and bioactivity in NaCaHs.  Rejection threshold models applied to NaCaHs with different bitter profiles.  Consumer rejection thresholds for the NaCaHs is influenced by the food matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The statistical methodology chosen to calculate rejection thresholds is important. Murray et al (2019) recently recommended that a complementary approach encompassing both RjT 50 and BET methodologies would be beneficial when estimating the acceptability of sensory properties. We observed that all rejection thresholds calculated by the BET approach were lower than those concentrations calculated using the graphical approach (RjT 50 ) (See Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The statistical methodology chosen to calculate rejection thresholds is important. Murray et al (2019) recently recommended that a complementary approach encompassing both RjT 50 and BET methodologies would be beneficial when estimating the acceptability of sensory properties. We observed that all rejection thresholds calculated by the BET approach were lower than those concentrations calculated using the graphical approach (RjT 50 ) (See Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5 ). Therefore, in agreement with Murray et al (2019) , BET are a conservative approach to determine acceptability. It may sometimes be more appropriate to use the BET methodology for products where acceptance is particularly important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation